SPIRIT RELIGI MASYARAKAT DESA TAMBAK ANYAR ULU DALAM MENINGKATKAN PARTISIPASI DI BIDANG PENDIDIKAN MADRASAH SWASTA - Rabini Sayyidati (P3M Politeknik Negeri Tanah Laut, 2016)
The strong phenomenon in religious spirit of Tambak Anyar Ulu people in participating for the education in private Islamic Madrasah self-dependently without any foundation to help them and without expecting government assistance are somewhat has become something unique. The research method used was qualitative method that was used to portray the cultural phenomenon in a rural community, particularly the participation of people in Tambak Anyar Ulu in the field of private Madrasah. The findings of this study are: 1) The forms of religious spirit activities of people of Tambak Anyar Ulu in an effort to increase their participation in the field of private madrasah education. 2) Religious spirit of teachers and learners in Madrasah Auladil Tarbiyyatul Islam’s education. 3) Madrasah Tarbiyyatul Auladil Islam is a pure private madrasah. 4) The people of Tambak Anyar Ulu were motivated to participate in Islamic education in private madrasah of Tarbiyyatul Auladil Islam compared to their participation in state public schools. In conclusion, the result of this research shows that the people of Tambak Anyar Ulu have been proven to be actively participating for the education in private Islamic Madrasah with the religious spirit as its baseline.